2016
DOI: 10.1177/1526602816641669
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Ultrasound–Derived Stent Dimensions as Predictors of Angiographic Restenosis Following Nitinol Stent Implantation in the Superficial Femoral Artery

Abstract: Postprocedure MSA can predict ISR in SFA lesions, which suggests that adequate stent enlargement during angioplasty might be required for superior patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…Generally, smaller stent area and longer lesion length are associated with restenosis after bare metal or drug-eluting stent implantation because neointimal proliferation occurs in any part of the stented segment and leads to lumen stenosis. 3,4 Our finding that no neointimal proliferation was found other than at the edges corresponds to a lack of association of lesion length and device diameter with restenosis.…”
Section: Discussionmentioning
confidence: 83%
“…Generally, smaller stent area and longer lesion length are associated with restenosis after bare metal or drug-eluting stent implantation because neointimal proliferation occurs in any part of the stented segment and leads to lumen stenosis. 3,4 Our finding that no neointimal proliferation was found other than at the edges corresponds to a lack of association of lesion length and device diameter with restenosis.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, it is very important to know the clinical features that may cause in-stent restenosis. It has been demonstrated that many parameters including diabetes mellitus, smoking, dyslipidemia, long complex lesions, and age are predictors of the in-stent restenosis after SFA interventions in the follow-up [ 16 , 17 ]. The rates of in-stent restenosis can be decreased by taking several precautions to these clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…If a significant adjusted mortality difference was found between races, a prespecified mediation analysis was planned to investigate the potential role of variations in procedural and postprocedural care in driving this difference. Procedural and postprocedural factors considered in the analyses included the following: (1) the use of advanced intracoronary imaging or physiologic testing (fractional flow reserve [FFR], 22 intravascular ultrasound [IVUS], 23 or optical coherence tomography [OCT]); (2) bare-metal stent (BMS) vs drug-eluting stent (DES) use; (3) incomplete revascularization; (4) radial access use; and (5) postprocedural medication prescriptions (high-intensity statins, β-blockers, angiotensin-converting enzyme inhibitor [ACEi] or aldosterone receptor blocker [ARB] therapy, and clopidogrel bisulfate, ticagrelor, or prasugrel). Performance of FFR, IVUS, or OCT included the use of this technology during the diagnostic catheterization, PCI, or both.…”
Section: Procedural and Postprocedural Carementioning
confidence: 99%